A study on blocking store-operated Ca2+ entry in pulmonary arterial smooth muscle cells with xyloketals from marine fungi - Zhou Jie-Bin; Sun Ying-Ying; Zheng Ying-Lin; Yu Chu-Qin; Lin Hua-Qing; Pang Ji-Yan (Acta Pharmaceutica, 2017)
In this study, the effect of four xyloketals 1-4 on store-operated calcium entry (SOCE) was investigated in primary distal pulmonary arterial smooth muscle cells (PASMCs) isolated from mice. The results showed that xyloketal A (1), an unusual ketal with C-3 symmetry, exhibited strong SOCE blocking activity. Secretion of interleukin-8 (IL-8) was also inhibited by xyloketal A. The parallel artificial membrane permeability assay (PAMPA) of 1-4 suggested that these xyloketals penetrated easily through the cell membrane. Moreover, the molecular docking study of xyloketal A with activation region of the stromal interaction molecule (STIM) 1 and the calcium release-activated calcium modulator (ORAI) 1 (STIM1-ORAI1) protein complex, the key domain of SOCE, revealed that xyloketal A exhibited a noncovalent interaction with the key residue lysine 363 (LYS363) in the identified cytosolic regions in STIM1-C. These findings provided useful information about xyloketal A as a SOCE inhibitor for further evaluation.